Effect of groove shape on mechanical properties of surface composites of Al 6082 prepared using friction stir processing. (2022) - Yadav, Sukhvir; Sharma, Sanjeev; Singh, Bhupender; Sharma, P.B.
Abstract: Aluminum-base surface composites have been fabricated by adding graphene oxide (GO) and graphite (GR) as reinforcement particles using friction stir processing to achieve higher strength, hardness, and percentage elongation. Two groove geometry as square groove and v-groove were utilized for preparing metal matrix composites. The reinforced particles distribution was investigated by microscope(2D) and scanning electron microscopy. The microstructures revealed a uniform distribution of reinforced particles in the case of square-grooved graphene oxide while the graphite composite was distorted structure. Graphene oxide derived from graphite by oxidizing its thinnest layer has been replacing the graphite as a substrate material used for surface composites fabricated during friction stir processing (FSP) of aluminum alloys. Additionally, Material Matrix Composite developed in FSP necessitated the improvement in mechanical properties. Additionally, the strength of the composite matrix was investigated under displacement control mode and the ultimate tensile strength of square grooved graphene oxide composite was 332 MPa and in the case of v-grooved graphite composite, it was 151 MPa.Similarly, percentage elongation was come out as 25.6 and 10.0 in the case of square grooved graphene oxide composite and v-grooved graphite composite respectively. Hardness values were investigated as 98.5 HV and 54.1HV square grooved graphene oxide composite and v-grooved graphite composite respectively This article assessed the impacts on mechanical properties and subsequently on the microstructure of Al-6082 T6 surface composite by varying groove shapes. Consequently, the choice between GO and GR as a reinforced material was also critically accredited.